2018
DOI: 10.1002/pds.4687
|View full text |Cite
|
Sign up to set email alerts
|

Understanding multi‐pill ingestion of prescription opioids: Prevalence, characteristics, and motivation

Abstract: Purpose Oral use is the primary route of administration among non‐medical prescription opioid users. While progression to non‐oral routes and shifts to stronger opioids have been previously studied as ways to cope with tolerance, the prevalence and patterns of those who cope by increasing the number of pills/tablets ingested at one time (ie, multi‐pill use) has not been assessed. Methods A subset (N = 231) of treatment‐seeking opioid users from a national opioid surveillance system, participating in the Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…21 Dietary supplementation with acetate, propionate, butyrate or their mixture can significantly inhibit the body weight gain induced by high-fat diet feeding. 22 Our study confirmed the positive effects of SCFAs on obesity.…”
Section: Discussionsupporting
confidence: 81%
“…21 Dietary supplementation with acetate, propionate, butyrate or their mixture can significantly inhibit the body weight gain induced by high-fat diet feeding. 22 Our study confirmed the positive effects of SCFAs on obesity.…”
Section: Discussionsupporting
confidence: 81%
“…SCFA also play a role in the balance of fatty acid synthesis, fatty acid oxidation, and lipolysis in the body's tissues through peroxisome proliferator-activated receptors [ 90 ]. Dietary supplementation with acetate, propionate, butyrate or their mixture can significantly inhibit the body weight gain induced by high-fat diet feeding [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of routes of administration reveals that the majority of participants who reported tapentadol ER abuse and ADF ER opioid abuse swallowed tablets whole (58.70% and 53.81%, respectively). Swallowing tablets whole is recognized as the primary pathway of nonmedical use [ 31 ], and ADFs do not surmount this route of administration. Taking more opioids than prescribed, generally, or swallowing more tapentadol than prescribed can result in side effects and possibly death [ 4 , 5 , 28 , 32–35 ].…”
Section: Discussionmentioning
confidence: 99%